2020
DOI: 10.3390/molecules25020346
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligonucleotides Containing 2′-N-alkylaminocarbonyl-2′-amino-LNA (2′-urea-LNA) Moieties Using Post-Synthetic Modification Strategy

Abstract: The post-synthetic modification of an oligonucleotide is a powerful strategy for the synthesis of various analogs of the oligonucleotide, aiming to achieve the desired functions. In this study, we synthesized the thymidine phosphoramidite of 2′-N-pentafluorophenoxycarbonyl-2′-amino-LNA, which was introduced into oligonucleotides. Oligonucleotides containing a 2′-N-pentafluorophenoxycarbonyl-2′-amino-LNA unit could be isolated under ultra-mild deprotection conditions (50 mM K2CO3 in MeOH at room temperature for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…A class of 2’-urea-LNA analogues ( 58–62 ) has been prepared by reacting various amine-functionalized groups with a 2'- N -pentafluorophenoxycarbonyl-2'-amino-LNA monomer already incorporated into an ON. All modifications improved hybridization towards both DNA and RNA complements when compared to natural DNA nucleotides [ 96 ].…”
Section: Reviewmentioning
confidence: 99%
“…A class of 2’-urea-LNA analogues ( 58–62 ) has been prepared by reacting various amine-functionalized groups with a 2'- N -pentafluorophenoxycarbonyl-2'-amino-LNA monomer already incorporated into an ON. All modifications improved hybridization towards both DNA and RNA complements when compared to natural DNA nucleotides [ 96 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, the 2′-nitrogen is suitable for advanced modifications by various chemical reactions during nucleic acid synthesis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Previous studies have reported the development of oligonucleotides (ONs), containing 2′-N-substituted ALNA derivatives, such as 2′-N-alkyl, 13,15 2′-N-acyl, 14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 2′-N-alkoxycarbonyl, 31 and 2′-N-alkylaminocarbonyl. 32 Sensor molecules such as fluorescent dyes, spin labels, and radioisotopes can be incorporated into 2′-amino groups for use as ONs in biological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Previous studies have reported the development of oligonucleotides (ONs), containing 2′-N-substituted ALNA derivatives, such as 2′-N-alkyl, 13,15 2′-N-acyl, 14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 2′-N-alkoxycarbonyl, 31 and 2′-N-alkylaminocarbonyl. 32 Sensor molecules such as fluorescent dyes, spin labels, and radioisotopes can be incorporated into 2′-amino groups for use as ONs in biological analysis. [14][15][16][17][18]22,23 ONs containing ALNAs functionalized fatty acid or sugar ligands into the 2′-nitrogen are expected to improve the pharmacokinetic profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation